Deviation of Trypsin Activity Using Peptide Conformational Imprints - Kiran Reddy Kanubaddi; Pei-Yu Huang; Ya-Lin Chang; Cheng Hsin Wu; Wei Li; Ranjith Kumar Kankala; Dar-Fu Tai; Chia-Hung Lee (Nanomaterials, 2021)
In this study, a methodology utilizing peptide conformational imprints (PCIs) as a tool to specifically immobilize porcine pancreatic alpha-trypsin (PPT) at a targeted position is demonstrated. Owing to the fabrication of segment-mediated PCIs on the magnetic particles (PCIMPs), elegant cavities complementary to the PPT structure are constructed. Based on the sequence on targeted PPT, the individual region of the enzyme is trapped with different template-derived PCIMPs to show certain types of inhibition. Upon hydrolysis, N-benzoyl-L-arginine ethyl ester (BAEE) is employed to assess the hydrolytic activity of PCIMPs bound to the trypsin using high-performance liquid chromatography (HPLC) analysis. Further, the kinetic data of four different PCIMPs are compared. As a result, the PCIMPs presented non-competitive inhibition toward trypsin, according to the Lineweaver-Burk plot. Further, the kinetic analysis confirmed that the best parameters of PPT/PCIMPs 233–245+G were Vmax = 1.47 × 10−3 mM s−1, Km = 0.42 mM, kcat = 1.16 s−1, and kcat/Km = 2.79 mM−1 s−1. As PPT is bound tightly to the correct position, its catalytic activities could be sustained. Additionally, our findings stated that the immobilized PPT could maintain stable activity even after four successive cycles.